Ethnographic accounts of linguistic issues in the Yugoslav successor states: An introduction - Kersten-Pejanić, Roswitha (Aegean Working Papers in Ethnographic Linguistics, 2019)
Doing ethnographic linguistics (or linguistic ethnography) in the area of what used to be Yugoslavia is both a challenging and a promising undertaking. Challenging, in that there are so many ideological traps to take into consideration. Promising, in that there are so many complex matters to take a closer look at. These matters, even when exclusively realized in linguistic means, may have great influence on people’s everyday political, cultural, and social meaning-making. Especially so, as indexical relations and the ideological premises and effects of choosing to use one linguistic realization over the other, has played an important role for all speech communities in the region.